Effect of Mindfulness-Based Breathing Exercise Combined with Lavender Aromatherapy on Anxiety and Sleep Quality among Hemodialysis Patients: A Quasi-Experimental Study - Yuwono, Trisno; Ellina, Agusta Dian; Prasetyo, Joko; Wahyuningsih, Atik Setiawan; Widyowati, Agustin (International Journal of Health Concord, 2025)
Background: Patients with chronic kidney failure report the sight of blood-filled dialysis tubes, the burden of routine therapy costs, fear of invasive measures, and the uncertainty of recovery triggers their anxiety. This anxiety also carries over into the home, causing difficulty sleeping at night and ongoing feelings of restlessness. Purpose. The Effect of the Combination of Mindfulness based on Breathing Exercise with Lavender Aromatherapy on Anxiety and Sleep Quality in Hemodialysis Patients Methods: This study employed a quasi-experimental pretest–posttest control-group design and was reported in accordance with the TREND guidelines for non-randomized intervention research. The target population comprised 90 hemodialysis patients at Bhayangkara Kediri Hospital, of whom 40 were selected using purposive sampling. The intervention consisted of a combination of mindfulness-based breathing exercises and lavender aromatherapy, with anxiety and sleep quality as outcome variables. Anxiety was measured using the Self-Rating Anxiety Scale (SAS), and sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), both of which have demonstrated acceptable validity and reliability in prior research. Data analysis included descriptive statistics and the Wilcoxon signed-rank test to determine pre-post differences between intervention and control groups, with a significance level set at p < 0.05. Result: The general characteristics of respondents were comparable between the intervention and control groups with respect to age, sex, duration of hemodialysis, and comorbid conditions. Specific baseline characteristics related to anxiety levels and sleep disturbances were also similar across groups, indicating initial equivalence. The Wilcoxon signed-rank test showed a statistically significant improvement in anxiety (p < 0.001) and sleep quality (p < 0.001) following the intervention. These findings suggest that combining mindfulness-based breathing exercises with lavender aromatherapy may reduce anxiety and enhance sleep quality among hemodialysis patients. Conclusion: The combination of mindfulness-based breathing exercises with Lavender Aromatherapy reduces Anxiety and improves Sleep Quality in hemodialysis patients. This intervention is very easy to implement, so it can be used as a nursing intervention in the hemodialysis unit to advance nursing science.